Jane Austen Reflections of a Reader - Bartlett, Nora (Open Book Publishers, 2021)
"This volume presents an exhilarating and insightful collection of essays on Jane Austen - distilling the author's deep understanding and appreciation of Austen's works across a lifetime. The volume is both intra- and inter-textual in focus, ranging from perceptive analysis of individual scenes to the exploration of motifs across Austen's fiction. Full of astute connections, these lively discussions hinge on the study of human behaviour - from family relationships to sickness and hypochondria - highlighting Austen's artful literary techniques and her powers of human observation. Jane Austen: Reflections of a Reader by (the late) Nora Bartlett is a brilliant contribution to the field of Jane Austen studies, both in its accessible style (which preserves the oral register of the original lectures), and in its foregrounding of the reader in a warm, compelling and incisive conversation about Austen's works. As such, it will appeal widely to all lovers of Jane Austen, whether first-time readers, students or scholars."